Birth Weight Status of the New Born Babies Born at Dhaka Medical College Hospital (TAJ: Journal of Teachers Association, 2009)
A cross-sectional study was carried out to determine the birth weight status of the newborn babies born at Dhaka Medical College Hospital as well as to find out the prevalence of low birth weight among them. All the new born babies (202) born at the labour room of Dhaka Medical College Hospital during the specified period were included in the study. Maximum newborn babies (78.71%) had birth weight 2.5Kg or more and 21.29% had low birth weight (